Assessing Dodd Frank effects on banking capital structure and Banker´s pay structure - Kawauti, Marcela de Carvalho Ponce (2014)
The systemic financial crisis that started in 2008 in the United States had some severe effects in the economic activity and required the bailout of financial institutions with the use of taxpayer’s money. It also originated claims for stronger regulatory framework in order to avoid another threat in the financial market. The Dodd Frank Act was proposed and approved in the United States in the aftermath of the crisis and brought, among many other features, the creation of the Financial Stability Oversight Council and the tougher inspection of financial institutions with asset above 50 billion dollars. The objective of this work is to study the causal effect of the Dodd Frank Act on the behavior of the treatment group subject to monitoring by the Financial Stability Oversight Council (financial institutions with assets above 50 billion dollars) regarding capital and compensation structure in comparison to the group that was not treated. We use data from Compustat and our empirical strategy is the Regression Discontinuity Design, not usually applied to the banking literature, but very useful for the present work since it allows us to compare the treatment group and the non-treatment group in the year of the enactment of the law (2010). No change of behavior was observed for the Capital Structure. In the Compensation Schemes, however, a decrease was found in the item other compensation for CEOs and CFOs. We also performed a robustness check by running a placebo test on the variables in the year before the law was enacted. No significance was found, which supports the conclusion that our main results were caused by the enactment of the DFA.